Association of Federal Mental Health Parity Legislation With Health Care Use and Spending Among High Utilizers of Services. Issue 4 (April 2019) - Haffajee, Rebecca L.; Mello, Michelle M.; Zhang, Fang; Busch, Alisa B.; Zaslavsky, Alan M.; Wharam, J. Frank
Abstract : Background: Decades-long efforts to require parity between behavioral and physical health insurance coverage culminated in the comprehensive federal Mental Health Parity and Addiction Equity Act. Objectives: To determine the association between federal parity and changes in mental health care utilization and spending, particularly among high utilizers. Research Design: Difference-in-differences analyses compared changes before and after exposure to federal parity versus a comparison group. Subjects: Commercially insured enrollees aged 18–64 with a mental health disorder drawn from 24 states where self-insured employers were newly subject to federal parity in 2010 (exposure group), but small employers were exempt before-and-after parity (comparison group). A total of 11, 226 exposure group members were propensity score matched (1:1) to comparison group members, all of whom were continuously enrolled from 1 year prepolicy to 1–2 years postpolicy. Measures: Mental health outpatient visits, out-of-pocket spending for these visits, emergency department visits, and hospitalizations. Results: Relative to comparison group members, mean out-of-pocket spending per outpatient mental health visit declined among exposure enrollees by $0.74 (1.40, 0.07) and $2.03 (3.17, 0.89) in years 1 and 2 after the policy, respectively. Corresponding annual mental health visits increased by 0.31 (0.12, 0.51) and 0.59 (0.37, 0.81) per enrollee. Difference-in-difference changes were larger for the highest baseline quartile mental health care utilizers [year 2: 0.76 visits per enrollee (0.14, 1.38); relative increase 10.07%] and spenders [year 2: $−2.28 (−3.76, −0.79); relative reduction 5.91%]. There were no significant difference-in-differences changes in emergency department visits or hospitalizations. Conclusions: In 24 states, commercially insured high utilizers of mental health services experienced modest increases in outpatient mental health visits 2 years postparity. Abstract : Supplemental Digital Content is available in the text.